1997
DOI: 10.1091/mbc.8.11.2291
|View full text |Cite
|
Sign up to set email alerts
|

End4p/Sla2p Interacts with Actin-associated Proteins for Endocytosis inSaccharomyces cerevisiae

Abstract: end4-1 was isolated as a temperature-sensitive endocytosis mutant. We cloned and sequenced END4 and found that it is identical to SLA2/MOP2. This gene is required for growth at high temperature, viability in the absence of Abp1p, polarization of the cortical actin cytoskeleton, and endocytosis. We used a mutational analysis of END4 to correlate in vivo functions with regions of End4p and we found that two regions of End4p participate in endocytosis but that the talin-like domain of End4p is dispensable. The N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
177
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(201 citation statements)
references
References 46 publications
22
177
2
Order By: Relevance
“…It has previously been reported that cells lacking Hip1 are, like yeast sla2 mutants, defective for endocytosis (Wesp et al, 1997;Metzler et al, 2003). We confirmed that A2 cells, expressing Hip1R at Ͻ10% of normal levels, also show a defect in transferrin internalization (Figure 2, A-C).…”
Section: Hip1r Depletion By Rnaisupporting
confidence: 87%
See 2 more Smart Citations
“…It has previously been reported that cells lacking Hip1 are, like yeast sla2 mutants, defective for endocytosis (Wesp et al, 1997;Metzler et al, 2003). We confirmed that A2 cells, expressing Hip1R at Ͻ10% of normal levels, also show a defect in transferrin internalization (Figure 2, A-C).…”
Section: Hip1r Depletion By Rnaisupporting
confidence: 87%
“…Deletion of SLA2, the budding yeast gene that encodes a Hip1R homologue, results in severe defects in actin organization, cell morphology, and endocytosis (Holtzman et al, 1993;Wesp et al, 1997;Yang et al, 1999). We therefore expected similar effects for A2 cells, which expressed Hip1R at the lowest levels.…”
Section: Hip1r Depletion By Rnaimentioning
confidence: 89%
See 1 more Smart Citation
“…The cdc50⌬ mutation exhibited synthetic lethality with ric1⌬ and a temperature-sensitive ypt6 mutation as well as rgp1 (our unpublished results), consistent with involvement of Cdc50p and Drs2p in endocytic recycling (Hua et al, 2002;Saito et al, 2004). Srv2p is also involved in endocytosis as a component of cortical actin patches (Wesp et al, 1997). Vps1p, a dynamin in yeast, has been implicated in clathrindependent protein transport at the TGN (Bensen et al, 2000;Gurunathan et al, 2002).…”
Section: Structural Integrity Of Ergosterol Is Required For Viabilitysupporting
confidence: 69%
“…This phenotype was specific to the cdc50⌬ erg3⌬ mutant and was not observed in actin-related mutants. Mutants of cortical actin patch assembly, sla2⌬ (Wesp et al, 1997) and myo3⌬ myo5-1 (Geli and Riezman, 1996), and actin cable assembly, tpm1-2 tpm2⌬ (Pruyne et al, 1998), assembled actin patches only at cortical sites (Figure 4, A and B), although, in the sla2⌬ mutant, some actin patches were localized at a short distance from the plasma membrane as described (Kaksonen et al, 2003). These results suggest that the actin cytoskeleton of the cdc50⌬ erg3⌬ mutant is disorganized in a fundamentally different manner from that of the known actin patch-or actin cable-deficient mutants.…”
Section: The Cdc50⌬ Erg3⌬ Mutant Intracellularly Assembles Cortical Amentioning
confidence: 99%